Effects of moisture absorption on the different modes of carbon/epoxy composites delamination. (July 2019) - Johar, M.; Chong, W.W.F.; Kang, H.S.; Wong, K.J.
Abstract: It is essential that moisture attack be considered when characterising interlaminar fracture toughness. However, limited work has been reported on the correlation between interlaminar fracture toughness of mixed mode I/II ratios and moisture content. Therefore, the present study aims to characterise the delamination of carbon/epoxy composites, immersed in distilled water at constant 70 °C. The specimens are tested at various water absorption levels using mode I, mode II and mixed-mode I/II loading configurations. The results revealed that mode I fracture toughness is insensitive to the moisture attack. However, approximately 50% drop in mode II and mixed-mode I/II fracture toughness are observed at high moisture content levels. Fibre bridging is also found in all wet specimens with an increment of up to 60–100% in fracture energy being observed for the tested water absorption levels. Upon water exposure, fractured surfaces are also found to possess a more porous matrix with a more significant fibre/matrix interface debonding. Through the study, a new three-dimensional criterion is proposed to characterise the variation of fracture toughness with both mode ratio and moisture content. The criterion is expected to allow for a better fundamental understanding with respect to the extent of moisture attack towards delamination of composite materials. Highlights: The moisture absorption exhibits non-Fickian behaviour. Mode I fracture toughness is invariant with the moisture content. Moisture attack reduced 50% of mode II and mixed-mode I/II fracture toughness. A maximum of 100% increment in fracture energy is noticed in wet specimens. Matrix porosity and fibre/matrix debonding are significant in aged specimens.